The Relationship between Knowledge Level and Fire Disaster Preparedness - Oktaviany Ayu Prawita Sari; Erika Dewi Noorratri (Inspirasi Foundation, 2023)
Objective: The purpose of this study was to determine the relationship between the level of community knowledge and fire disaster preparedness in Gedongan Village. Method: The method used is a quantitative method with a correlational research design. The population in the study was 3,961 residents. The sample in this study amounted to 97 residents who were selected based on the purposive sampling method with Spearman-Rho statistical analysis. Result: The results of the univariate analysis of this study were that 89.7% of respondents had good knowledge, 10.3% had sufficient knowledge, 9.3% had sufficient preparedness, and 90.7% had good preparedness. Conclusion: The results of the bivariate analysis in this study show that the p value is 0.000 with a coefficient of 0.771, which means that there is a very strong relationship between the variables of knowledge and preparedness in Gedongan Village.